Drought coping strategies in cotton: increased crop per drop. Issue 3 (March 2017) - Ullah, Abid; Sun, Heng; Yang, Xiyan; Zhang, Xianlong
Summary: The growth and yield of many crops, including cotton, are affected by water deficit. Cotton has evolved drought specific as well as general morpho‐physiological, biochemical and molecular responses to drought stress, which are discussed in this review. The key physiological responses against drought stress in cotton, including stomata closing, root development, cellular adaptations, photosynthesis, abscisic acid (ABA) and jasmonic acid (JA) production and reactive oxygen species (ROS) scavenging, have been identified by researchers. Drought stress induces the expression of stress‐related transcription factors and genes, such as ROS scavenging, ABA or mitogen‐activated protein kinases (MAPK) signalling genes, which activate various drought‐related pathways to induce tolerance in the plant. It is crucial to elucidate and induce drought‐tolerant traits via quantitative trait loci (QTL) analysis, transgenic approaches and exogenous application of substances. The current review article highlights the natural as well as engineered drought tolerance strategies in cotton.